Place names as markers of the dialects and sub-dialects of Tuvan language - Bavuu-Surun, Mira V. (The New Research of Tuva, 2018)
In this article we propose that place names should be considered markers of the dialects and sub-dialects of the Tuvan language, which is a new perspective on the toponymy of Tuva. Tuvan language is divided into the following dialects and sub-dialects: the Central dialect with Dzun-khemchik, Erzin-tes-khem, Ulug-khem, Ovyur and Tandyn sub-dialects; the Western dialect with Bai-taiga-barun-khemchik, Mongun-taiga, Kara-hol sub-dialects; Tere-hol, Todzha, Tsagaan-nur dialects; and finally, Altai dialect with Kobdo, Tsengel and Chinese sub-dialects. The modern dialect features of Tuvan language are a result of both interdialectal and interlanguage contacts and development of the language’s own resources. The place names of Tuva reflect a state of the language relations: the Central and the Western dialect with their sub-dialects occupy the vast territory of the modern Tuva, where the Turkic and original Tuvan toponyms are found, which are clear in their etymology. Rare mongolisms - toponyms occurring in the territory of Central and Western dialects - reflect historical Turkic-Mongolian language connections. Micro-toponyms of the Mongolian origin are located more densely in the south-east of the modern Tuva, especially in the areas where Erzin-tes-khem sub-dialect and Tere-hol dialect are spoken. The Todzha dialect area is known for its complex toponyms, including components of the ancient Turkic origin, which do not occur in other areas of Tuvan language. These toponyms reflect the richness of the flora and fauna of the taiga. The endemic appellative “khem” unites Mongolian and Chinese territories which have always been home for ethnic Tuvans - native speakers of Tsengelsky and Altai sub-dialects. This area also covers the border territories between Tuva and Gorny Altai, where over time Tuvan tribal groups were assimilated. Finally, in the areas where foreign dialects of Tuvan are spoken, toponymy has developed parallel Tuvan-Kazakh or Tuvan-Mongolian names for the same location; while Tuvan-Russian parallel names appear in the territories of the Central dialect, where the Old Believers began to settle down since the beginning of the 20th century.